2011
DOI: 10.1007/s11273-011-9209-3
|View full text |Cite
|
Sign up to set email alerts
|

Where is the avoidance in the implementation of wetland law and policy?

Abstract: Many jurisdictions in North America use a ''mitigation sequence'' to protect wetlands: First, avoid impacts; second, minimize unavoidable impacts; and third, compensate for irreducible impacts through the use of wetland restoration, enhancement, creation, or protection. Despite the continued reliance on this sequence in wetland decision-making, there is broad agreement among scholars, scientists, policymakers, regulators, and the regulated community that the first and most important step in the mitigation sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 78 publications
(101 reference statements)
0
81
0
2
Order By: Relevance
“…For example, Clare, Krogman, Foote & Lemphers [8] state that "many jurisdictions in North America use a 'mitigation sequence' to protect wetlands: First, avoid impacts; second, minimize unavoidable impacts; and third, compensate for irreducible impacts through the use of wetland restoration, enhancement, creation, or protection". McKenney & Kiesecker [9] also refer to 'steps in a sequence' and Ekstrom et al [2] define the mitigation hierarchy as "the sequence of actions…" With this, it was suggested that the word sequence appeared to be a far more accurate and potentially less confusing or misleading description of the ordered series of mitigation interventions that must be considered for efficient and effective impact management.…”
Section: Mitigation Hierarchy or Mitigation Sequencementioning
confidence: 99%
“…For example, Clare, Krogman, Foote & Lemphers [8] state that "many jurisdictions in North America use a 'mitigation sequence' to protect wetlands: First, avoid impacts; second, minimize unavoidable impacts; and third, compensate for irreducible impacts through the use of wetland restoration, enhancement, creation, or protection". McKenney & Kiesecker [9] also refer to 'steps in a sequence' and Ekstrom et al [2] define the mitigation hierarchy as "the sequence of actions…" With this, it was suggested that the word sequence appeared to be a far more accurate and potentially less confusing or misleading description of the ordered series of mitigation interventions that must be considered for efficient and effective impact management.…”
Section: Mitigation Hierarchy or Mitigation Sequencementioning
confidence: 99%
“…The reluctance of the ECJ vis-à-vis novel mitigation strategies under the generic decision-making procedures laid down by the Habitats Directive appears justified. The risk that such a flexible mitigation strategy would undercut the crucial prior steps in the mitigation hierarchy should not be underestimated (Clare et al 2011).…”
Section: Mitigation Hierarchy: Restoration Actions As a Last Resort Omentioning
confidence: 99%
“…There is broad agreement among scholars, scientists, policymakers, and regulators that the first and most important step in the mitigation hierarchy, avoidance, is ignored more often than it is implemented (i.e., [28]). Developing criteria to determine whether impacts should be avoided altogether will be a key challenge when offsets are an available option, as there are limits to what can be offset [29].…”
Section: Principle 1 Environmental Offsets May Not Be Appropriate Fomentioning
confidence: 99%